Strategic guidelines for community enterprise development: a case in rural Thailand - Harry Jay Cavite; Chanhathai Kerdsriserm; Suneeporn Suwanmaneepong (Journal of Enterprising Communities People and Places in the Global Economy, 2021)
Purpose In spite of the government’s support for small-scale rice farmers in rural areas of Thailand, several problems still affect their production and marketing performance. This study aims to assess a rice production community enterprise (RPCE) through an in-depth investigation of its problems and capabilities; and formulate internal strategic guidelines for enterprise development. Design/methodology/approach This study used a qualitative approach through in-depth interviews with the community enterprise leader and committee members, and focus group discussion with eight farmer-members, purposively selected in Chachoengsao, Thailand. Data were transcribed, sorted and organised to determine themes and patterns. Strengths, weaknesses, opportunities and threats (SWOT) and threats, opportunities, weaknesses and strengths (TOWS) matrix situational analyses were done to develop strategic options. Strategic guidelines were formulated through a final deliberation with all members to ensure strategies aligned with the enterprise’s goals and objectives. Findings The results have identified three main problem categories encountered by the community enterprise in the areas of membership and labour; production and milling operations; and product design and marketing. The enterprise’s main strengths and opportunities include its product certifications and support from external organisations. Strategic points were developed, and policy support programmes are recommended for capacity building and product development as most problems identified relate to these aspects. Originality/value The utility of this study is its focus on an RPCE. The findings will help policymakers and concerned government agencies implement better programmes and policies to develop RPCEs. Furthermore, this study will be a source for future qualitative literature that will provide helpful information to other studies aiming to develop other types of community enterprises (CEs).
Keywords: Accounting and Organizational Management; Global and Cross-Cultural Management; Quality and Supply Management